Agonistic sounds and swim bladder morphology in a malapterurid electric catfish. (31st March 2015) - Boyle, K. S.; Bolen, G.; Parmentier, E.
Abstract Several catfish families possess an elastic spring apparatus (ESA) morphology that is assumed to function as a swim bladder drumming sound production mechanism. Although they have an ESA, drumming sounds in the electric catfish (Malapteruridae) have not been described. We have recorded several different sound types in Malapterurus beninensis and we examined the morphology of the swim bladder, the ESA and the ultrastructure of the protractor muscle. The protractor muscle contains small rounded muscle fibers with abundant mitochondria, narrow myofibrils, elaborated sarcoplasmic reticula and sometimes sarcoplasmic cores. Contractions of the protractor muscle should pull the Müllerian ramus (MR) and attached swim bladder anteriorly. Further, the MR possesses an anterior fulcrum that abuts upon the vertebral complex. Several sound types were elicited during agonistic interactions in the laboratory. We observed ratchet, click train and mouth sounds. Mouth sounds are single event, low‐frequency (mean dominant frequency 176 Hz) sounds that coincide with a bite‐like motion. Ratchet and click sounds are high‐frequency (mean dominant frequency 1568 and 3739 Hz, respectively) and occur in trains. Ratchet and click train sound characteristics are not indicative of a muscle‐driven drumming sound predicted by ESA morphology. We propose several hypotheses for these sound production mechanisms. Click sounds, in particular, could result from gas movement through the neck between the anterior and posterior swim bladder chambers.